2019
DOI: 10.1177/1744806919881846
|View full text |Cite
|
Sign up to set email alerts
|

Rat NaV1.7 loss-of-function genetic model: Deficient nociceptive and neuropathic pain behavior with retained olfactory function and intra-epidermal nerve fibers

Abstract: Recapitulating human disease pathophysiology using genetic animal models is a powerful approach to enable mechanistic understanding of genotype-phenotype relationships for drug development. Na V 1.7 is a sodium channel expressed in the peripheral nervous system with strong human genetic validation as a pain target. Efforts to identify novel analgesics that are nonaddictive resulted in industry exploration of a class of sulfonamide compounds that bind to the fourth voltage-sensor domain of Na V 1.7. Due to sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The tissues were sectioned, fixed and dehydrated as described above. Following PAP-pen labeling, IHC was performed as described above but using a knockout-validated [19] mouse monoclonal antibody (mouse-anti-Nav1.7; cloneN68/6; NeuroMab; RRID:AB_10672976; 1:250) and with secondary antibody (goat-anti-mouse IgG1 555; 1:2000).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…The tissues were sectioned, fixed and dehydrated as described above. Following PAP-pen labeling, IHC was performed as described above but using a knockout-validated [19] mouse monoclonal antibody (mouse-anti-Nav1.7; cloneN68/6; NeuroMab; RRID:AB_10672976; 1:250) and with secondary antibody (goat-anti-mouse IgG1 555; 1:2000).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…According to the manufacturer's datasheet, the antibody recognizes the expected monomeric (230 kDa) band for Nav1.7 on cell lysates of transfected HEK cells and does not cross-react with other Nav channels. The antibody has been knockout-validated using immunocytochemistry on mouse cultured DRG neurons and using IHC on rat brain (Grubinska et al, 2019). We have also recently shown that this antibody robustly stains human DRG and shows a specific and similar expression pattern to its mRNA (Shiers et al, 2020).…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…The tissues were prepared, fixed and dehydrated as described above. Following PAP-pen labeling, IHC was performed as described above but using a knockout-validated [18] mouse monoclonal antibody (mouse-anti-Nav1.7; cloneN68/6; NeuroMab; RRID:AB_10672976; 1:250) and with secondary antibody (goat-anti-mouse IgG1 555; 1:2000).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%